Completely epicardial implantable cardioverter/defibrillator (ICD) and CRT‐D systems: A case series and systematic literature review. Issue 9 (2nd August 2021) - Tonko, Johanna B.; Blauth, Christopher; Rosenthal, Eric; Rinaldi, Christopher A.
Abstract: Background: Epicardial ICD systems and CRT‐Ds using high voltage coils represent an alternative to transvenous systems in patients without central venous access and prior device complications including infection. Objective: We present a case series in the adult population of epicardial ICD/CRTD systems using high voltage epicardial coils. We summarize the existing data regarding techniques, efficacy, and safety. Methods: A retrospective board approved medical record review was conducted for all patients undergoing epicardial ICD/CRTD placement at our institution between January 2010 and May 2020. The literature was reviewed for prior published trials, case reports, and case series of epicardial high voltage coil insertions. Results: Eleven patients (six female, mean age 48 years) underwent epicardial ICD/CRTD implant including 5/11 completely epicardial CRTD systems. The procedure was performed via median sternotomy in eight patients, left anterior thoracotomy in two patients, and sub‐xiphoid approach in one patient. After a mean follow up of 35 months, appropriate successful shocks were delivered in two (18%) patients and no patients received an inappropriate shock. Three of five (60%) patients had volumetric remodeling with CRT with significant improvement of LV EF. Device‐related complications requiring a surgical/percutaneous revision or another DFT test occurred in six patients (54%). One patient died during follow up due to refractory heart failure. No cases of epicardial device infection, coronary artery compression, constrictive pericarditis, or erosion of defibrillator coils into intrathoracic organs were reported. No randomized studies comparing safety and efficacy of traditional transvenous or subcutaneous ICD systems and epicardial ICD systems using contemporary high voltage coils were found nor any studies directly comparing epicardial defibrillator patches versus epicardial coils. Thirteen case series and 24 single case reports published between 2004 and 2020 were identified describing in total a heterogenous group of 188 patients with ICD systems incorporating one or more epi‐ or pericardially positioned shock coils. Conclusion: The use of epicardial defibrillation coils for ICD/CRT‐D is a feasible treatment option for patients with either failed or contraindicated transvenous ICD systems. Dedicated epicardial high voltage leads with integrated pace‐sense electrodes and specialized delivery tools for minimal invasive implantations may improve longer term outcomes.